2022
DOI: 10.1364/oe.451264
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pulse self-compression in hollow capillary fibers using decreasing pressure gradients

Abstract: The improvement of techniques for the generation of near-infrared (NIR) few-cycle pulses is paving the way for new scenarios in time-resolved spectroscopy and the generation of ultrashort extreme-ultraviolet pulses through high-harmonic generation. In this work, we numerically study how to optimize the self-compression of NIR pulses using decreasing pressure gradients in hollow capillary fibers (HCFs). We identify a moderate nonlinear regime in which sub-cycle pulses are obtained with very good temporal qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…2(a) reached a sub-cycle full width at half maximum (FWHM) duration of 1.1 fs, corresponding to a peak power of 10.9 GW. Similar results were obtained at other energies and gas pressures lying in the optimal region [7].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…2(a) reached a sub-cycle full width at half maximum (FWHM) duration of 1.1 fs, corresponding to a peak power of 10.9 GW. Similar results were obtained at other energies and gas pressures lying in the optimal region [7].…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, we have obtained a simple relation between the input pressure and the pulse energy based on the B-integral which allows to place the optimal region for self-compression in the 2D parameter space [7]. One of the output pulses along this curve is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To select the right parameters for the self-compression effect, we have to take into account that the linear dispersion experimented by the laser pulse inside the HCF depends on the gas dispersion and the HCF contributions. Moreover, the nonlinear response depends not only on the gas properties and pressure configuration [24], but also on the mode confinement. For instance, since both linear and nonlinear propagation properties depend on the spatial profile of the beam inside the capillary (see section 2.3 for an explanation of the HCF spatial modes), the use of high order hybrid modes [25][26][27] or structured beams with different number of lobes [28,29] have been proposed to obtain self-compression in HCFs.…”
Section: Pulse Soliton Self-compression In Hcfsmentioning
confidence: 99%
“…These simple fibers are routinely used for ultrashort pulse compression and allow for significant energy scaling and nonlinearity and dispersion tuning by modifying the pressure of the filling gas . In particular, if the latter is chosen so that an input multicycle pulse propagates in the HCF with anomalous dispersion, the simultaneous nonlinear spectral broadening by self-phase modulation (SPM) and phase compensation arising from the negative group-velocity dispersion (GVD) can lead to soliton self-compression well down into the subcycle regime. , Recent studies have demonstrated that this extreme pulse compression can be further enhanced by pumping the fiber with a decreasing pressure gradient and that broadly similar high-quality subcycle IR fields can be generated in different HCF scenarios . In addition, the use of decreasing pressure could be of great interest for HHG experiments, as it allows for the direct delivery to vacuum of the self-compressed pulses free of distortions from transmission optics. , Altogether, the combination of HHG beamlines with HCFs delivering intense self-compressed IR transients opens a very promising scenario to develop compact and versatile scientific tools for the generation of high-frequency IAPs, but theoretical investigations and design guidelines are still missing to make it a feasible technique.…”
Section: Introductionmentioning
confidence: 99%